Calculated Changes in the Elastic Properties of MgCNi3 at the Superconducting Transition - R. Abd-Shukor (Advances in Materials Science and Engineering)
We calculated the elastic properties of MgCNi3 at the superconducting transition () using various thermodynamic and acoustic data. From the calculations, a step discontinuity of 8 ppm in the bulk modulus, 7 ppm in the Young’s modulus, and 3 ppm in the longitudinal sound velocity () is expected at . The step discontinuities at the transition temperature indicated the importance of lattice changes to the superconducting mechanism of MgCNi3. The Debye temperature was calculated to be 460 K. The electron-phonon coupling constants calculated in the weak and strong coupling limits of the BCS theory and the van Hove scenario showed that MgCNi3 is a moderately strong coupled superconductor.